2013
DOI: 10.1021/bi401270d
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RNA–Protein Interactions within the Human Immunodeficiency Virus Type 1 Lifecycle

Abstract: RNA–protein interactions are vital throughout the HIV-1 life cycle for the successful production of infectious virus particles. One such essential RNA–protein interaction occurs between the full-length genomic viral RNA and the major structural protein of the virus. The initial interaction is between the Gag polyprotein and the viral RNA packaging signal (psi or Ψ), a highly conserved RNA structural element within the 5′-UTR of the HIV-1 genome, which has gained attention as a potential therapeutic target. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Macrophages secrete virions from virus-containing intracellular vacuoles (41). Late endosomes are the principal locations for HIV assembly (42)(43)(44)(45)(46). Importantly, nanoATV retains full antiretroviral activity in late endosomes, as RT activity was substantially decreased in Rab7 and Rab11 vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages secrete virions from virus-containing intracellular vacuoles (41). Late endosomes are the principal locations for HIV assembly (42)(43)(44)(45)(46). Importantly, nanoATV retains full antiretroviral activity in late endosomes, as RT activity was substantially decreased in Rab7 and Rab11 vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…A FRET based SL3 RNA melting assay, similar to the cTAR DNA melting assay (Shvadchak et al, 2009) where the 3’ and 5’ ends of the oligonucleotide are labeled with a TET fluorophore and a black hole quencher (BHQ1), was used by Bell et al to identify a SL3-Gag interaction to identify compound 18 (Fig 5) (Bell et al, 2013). Using NMR studies, compound 18 was shown to interact with the tetraloop of the RNA, which is the region that is required for NC binding.…”
Section: Rna Bindersmentioning
confidence: 99%
“…They had shown earlier that NC is sufficient to bind SL3 RNA, however, the chaperoning effect is significant only in the presence of the flanking domains of the Gag polyprotein (Bell et al, 2012). Bell and colleagues hypothesized that the specific ability of Gag polyprotein, rather than mature NC, could effect structural changes in SL3 which may aid in genomic viral RNA packaging into the virus particle though avoiding binding by prematurely cleaved NC (Bell et al, 2013). This is in contrast with the significant chaperoning of NC alone on the TAR/cTAR oligonucleotides (Godet and Mely, 2010; Levin et al, 2010; Shvadchak et al, 2009; Sosic et al, 2013).…”
Section: Rna Bindersmentioning
confidence: 99%
“…3D). These include TAR 154 and RRE, 155 but also the dimer initiation sequence (DIS), 156 the packaging signal (Ψ), 157 and the Gag/Pol frameshifting signal. 34 The TAR element resides within the 5′ UTR of the viral genome and serves as the binding site for the Tat protein.…”
Section: Viral Rna Motifsmentioning
confidence: 99%